Justified. The complete third season [videorecording (DVD)] - Olyphant, Timothy; McDonough, Neal; Searcy, Nick; Carter, Joelle; Goggins, Walton, 1971- (Sony Pictures Home Entertainment, 2012)
Season three introduces a new main villain, Robert Quarles of Detroit. The parent criminal organization connected to the Frankfort mafia has exiled Quarles to Kentucky. Quarles begins to muscle in on the local criminals, successfully supplanting them until Raylan begins investigating. Simultaneously, Dickie Bennett, the lone survivor of the Bennett clan, seeks the aid of the black residents of Noble's Holler and their leader Ellstin Limehouse in recovering his inheritance.